Persepsi Generasi Muda terhadap Minat Bertani di Kawasan Pariwisata Tanah Lot (Kasus Subak Gadon III, Tabanan) - LOSVITASARI, NI MADE; DIARTA, I KETUT SURYA; SURYAWARDANI, I GUSTI AYU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Perception of Young Generations’ Interest in Farming in Tanah Lot Tourism Area (The Case of Subak Gadon III, Tabanan) The rapid development of tourism will affect subak : that is, the transformation of labor, the occurrence of land conversion, and the occurrence of water use competition. Tourism will have an impact on farming interest, especially the younger generation of farm households in Subak Gadon III, knowing that this subak is located in the tourism area. The purpose of this study was to analyze perceptions and differences in the perception of younger generation of non-tourism and younger generation of tourism about the impact of tourism on farming interest of the younger generation of farm households in Subak Gadon III, Tabanan. Data analysis method used was descriptive-qualitative and quantitative. The results showed that the perception of the younger generation of non-tourism about the impact of tourism on the farming interest of the younger generation was classified with a score of 3,32. The younger generation of non-tourism had a perception that the existence of tourism sufficiently influenced the farming interest of the young generation, but it did not make the non-tourism youth switch to tourism. The younger generation of tourism showed that tourism had a high impact on the interest of farming the younger generation with a score of 3,55. The young generation of tourism has a perception that tourism was the most appropriate choice because for them the tourism sector is very supportive of its life. There is a difference in the impact of tourism on farming interest in the younger generation of non-tourism and young generation of farm households' tourism in Subak Gadon III, Beraban, Tabanan. This difference was seen in 3 parameters of a total of 14 parameters. Suggestions that can be made for this research are for Subak Gadon III in the future to be able to initiate a new breakthrough by involving the young generation in various activities in subak life to attract farmers especially the younger generation of farm households in Subak Gadon III, Tabanan.